Sweeney Todd movie soundtrack [compact disc] - Depp, Johnny; Rickman, Alan; Bonham Carter, Helena, 1966-; Baron Cohen, Sacha, 1971- (Nonesuch, 2007)
Stephen Sondheim's most celebrated and operatic work gets the Tim Burton treatment with a bold and ambitious orchestration. Features highlights from the film, including Johnny Depp's debut as a singer.